Letter from Malaysia: advancing respiratory frontiers through innovation, education, and collaboration - Ismail, Ahmad Izuanuddin (2025)
As malaysia transitions into the post- pandemic era, the malaysian thoracic society (mts) continues to redefine respi- ratory medicine through education, service development, ad- vocacy, and international collaboration. The 2024–2025 period marked further expansion of the society’s reach, deeper engage- ment across healthcare sectors, and significant elevation of the national discourse on lung health.